The Effect of Organizational Justice on Innovation Behavior with Affective Commitment as a Mediation Variable - Bambang Hariono; Adi Rahmat; Fahmi Oemar (Yayasan Education Al Aqsho Modern, 2022)
This research was conducted in the Public Sector of the Indragiri Hilir Regency Government with the aim of identifying the impact between organizational justice, innovation behavior and affective commitment. It also aims to explain the mechanism underlying the relationship between organizational justice, innovation behavior and affective commitment. In this case, the total population is 53 people, so that the population form is included in the non-probability sampling category by using a self-administered questionnaire. The distribution of the questionnaires will be carried out using a convenience sampling method and hypothesis testing in this study using SEM-PLS through WarPLS 5.0 software. PLS is a structural equation analysis (SEM) the results in this study prove that organizational justice has a positive effect on affective commitment, organizational justice has a positive and significant effect on innovation behavior and affective commitment mediates the effect of organizational justice on innovation behavior. The limitation of this research is that the small population taken is less able to generalize the research results, especially those that describe the moderating role of organizational justice between Affective Commitment and Innovation Behavior.